DEVELOPMENT OF DIGITAL TEACHING MATERIALS TO SUPPORT LEARNING INDEPENDENCE FOR 5TH GRADE ELEMENTARY SCHOOL STUDENTS - Hendracipta, Nana; Syachruroji, A. (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2023)
AbstractThe need for teaching materials is crucial in supporting the learning process, particularly in online-based learning where digital-based teaching materials are highly necessary. Therefore, this research developed digital teaching materials about the concept of ecosystems in elementary schools. The purpose of this research was to develop teaching materials that meet validity criteria and receive positive feedback from students as users. The research method used was research and development. The data collection techniques used were literature review, questionnaires, and documentation. The data analysis technique used was descriptive data analysis through quantitative analysis of the questionnaire, then it was interpreted qualitatively to obtain the feasibility of digital teaching materials and describe students’ responses to the application of digital teaching materials. The results showed that the content validity was “very good”, while the presentation and language validity were in the “good” category. The media validity was categorized as “feasible”. In this case, the software element obtained a “very good” category, and the visual communication element obtained a “good” category. Furthermore, the average student response showed a positive reaction to digital-based teaching materials, with the appearance and presentation aspects rated as “strongly agree” and the benefit aspect rated as “agree”. Keywords: Digital Teaching Materials; Ecosystem